PENYULUHAN TEKNOLOGI PENGOLAHAN LIMBAH UNGGAS MENJADI PRODUK BERDAYA JUAL TINGGI DALAM MENINGKATKAN PENDAPATAN DI DESA KATUMBANGAN KECAMATAN CAMPALAGIAN POLEWALI MANDAR - Dameria Haloho, Ruth; Irfan, Muhammad; Parawansa Sarman, Aco; Ceria, Yuni (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Katumbangan Village is a village in Polewali Mandar District, Polewali Mandar Regency, where the majority of the population is farming and gardening. Katumbangan Village, like other areas in Polewali Mandar Regency, has a fairly large population of chicken farms, so the amount of chicken meat and by-products is quite large. With this potential, the Women Farmers Group conducted training on poultry waste processing, namely the manufacture of intestinal and claw chips with the aim of providing new knowledge and skills in the manufacture of processed poultry waste products, marketing, and monitoring. The results of implementing community service in processing poultry waste and claws are that participants understand the manufacture of intestines and claw chips by 95%, participants are able to understand and know how to make intestine and claw chips as well as poultry waste processing technology by 90%, participants are able to package poultry waste products, participants interested in starting a business selling claws, participants were able to calculate the profit from selling claws as much as 85%. The benefits felt by participants were increased knowledge and skills in processing intestine and claw chips. The income that can be obtained from selling claw and intestine chips is IDR 35,000/kg. This community service activity must be further developed, so as to be able to produce large-scale intestinal and claw chips which can open up jobs and absorb labor.